Effects of Pivot Windows and Wing Walls on Single Sided Natural Ventilation in Rumah Susun (Walk Up Flat) - Prihatanti, Nilla Ardya; Ekasiwi, Sri Nastiti Nugrahani; Defiana, Ima (Institut Teknologi Sepuluh Nopember, 2020)
Rumah susun (walk up flat) are one of the buildings that rely on natural ventilation. However, the application of natural ventilation in rumah susun (walk up flat) in urban areas is influenced by tropical climate problems such as high temperatures and low wind speeds. The design of the openings in the facade has not been able to distribute air into rooms properly. In addition, the layout design makes single-sided natural ventilation the only strategy possible for double loaded corridor type flat. This study aimed to determine the effect of a combination of pivot window designs and wing walls in directing and distribute air into room. The study was conducted in two stages, that was field measurements and experimental with Computational Fluids Dynamics simulations. Simulations were conducted on a combination designs of wing walls and pivot window with 45o and 90o opening angles to determine their effects on the distribution and indoor air velocity. The combination design of wing walls and pivot window created a pressure difference so that it could increase indoor air velocity under both oblique and parallel to the opening. In the direction of the wind that was not oriented to the openings, the combination of wing walls and vertical pivot windows with 90o opening angles increased indoor air velocity up to five times in the corner room. While the 45o opening angle increased the indoor air velocity up to seven times than base case condition in a middle room.